Architectural Forms of Collective Memory. Issue 1 (5th July 2019) - Moliner, Pascal; Bovina, Inna
In 2015, the Moscow City Hall and the Gulag History Museum launched a competition for the creation of a commemorative monument dedicated to the victims of political repression in Russia during the 1920s to the 1950s. In this article we present three studies carried out on an array of 309 images (digital images, model photographs, drawings) related to the projects submitted for this competition. Each project image was accompanied by a text written by the author (artist, architect, designer). These images and texts were analyzed within the framework of the concept of collective memory and the theory of social representations. The first study focused on the texts and suggested that there are two dimensions of the collective memory about the commemorated event, a historical dimension and a human dimension. The second study focused on images, two dominant forms in the monument projects were identified. The third study showed that depending on whether the accompanying text favors the historical dimension of the event or its human dimension, the designers did not make identical use of the different architectural forms (identified in the previous study) to elaborate their project. These results suggest that the architectural forms of monument projects vary according to the historical vs. human dimension favored by the collective memory of their authors.